Un-sitely mediations - Robyn Holly Taylor-Neu (Semiotic Review, 2024)
This essay explores the critical affordances of animated citationality through ethnographic engagement with independent animation filmmakers and analysis of a scene in the animated short film Have a Nice Dog! (2020), by Damascus-born, Berlin-based filmmaker Jalal Maghout. I develop the notions of animated citationality and displaced agency to underscore how animated relays of agency (Manning & Gershon 2013; Gell 1998) and the semiotic dimensions of “liveliness” (Silvio 2010; Cholodenko 2014) entwine with practices of citation that reflexively displace discursive events from their contexts of emergence (Nakassis 2013; Derrida 1988; Butler 1997). Here, I argue that Maghout uses animation’s citational affordances to illuminate the tension between experiences of mediated freedom and geopolitical constraint. His film confronts us with a troubling chiasm: in the context of ramifying border regimes, the mobility of signs and their citations becomes inversely proportionate to the mobility of (some) persons.